CLABSI Reduction Strategy: A Systematic Central Line Quality Improvement Initiative Integrating Line-Rounding Principles and a Team Approach. (June 2016) - Wilder, Kerry A.; Wall, Brittany; Haggard, David; Epperson, Tiffany
Abstract : Background: Central line–associated bloodstream infections (CLABSIs) are the most common hospital-acquired infections costing hospitals millions of dollars annually. An evidence-based practice literature review revealed that utilizing a systematic team approach for proper line maintenance is effective in reducing CLABSI rates. Purpose: The purpose of this quality improvement initiative was to reduce the CLABSI rate in the neonatal intensive care unit from 3.9 per 1000 line days in 2011 by at least 50% in 2014. Policies, protocols, team members utilized, competencies, and techniques were created and a formal line-rounding and dressing change competency was established. The competency included specific criteria for performing daily line rounds and a 2-person sterile technique for dressing changes. Findings/Results: Central line–associated bloodstream infection rate was effectively reduced from 3.9 in 2011 to 0.3 per 1000 line days in 2014, with an overall 92% improvement. Implications for Practice: Introduction of a dedicated CLABSI team has been shown to be effective in the reduction of CLABSI rates in the neonatal intensive care unit. Implications for Research: Further research is needed to evaluate how a team approach could be used to reduce other hospital-acquired conditions; catheter-associated urinary tract infection, and hospital-acquired pressure ulcers.